Molecular and morphological data support the transfer of the monotypic Iranian genus Alococarpum to Prangos (Apiaceae) - Lyskov, Dmitry F.; Samigullin, Tahir H.; Pimenov, Michael G. (Phytotaxa, 2017)
Based on molecular and morphological evidence, the monotypic genus Alococarpum endemic to Iran has been transferred to the genus Prangos (as P. eriantha (DC.) Lyskov & Pimenov comb. nov.). The main diagnostic characters of fruits (shape of endosperm, division of mesocarp, presence of cyclic vittae and diffuse vascular bundles) are the same both in Prangos and Alococarpum. Our molecular analysis of nrITS/ETS markers also supported the monophyly of Prangos including Alococarpum.